Open channel block of Kv1.5 channels by HMQ1611 - Dong, Chao; Li, Jiawei; Ding, Weiguang; Ueda, Rika; Xie, Xiaolu; Wu, Jie; Matsuura, Hiroshi; Horie, Minoru (Frontiers in Pharmacology, 2022)
Kv1.5 channels conduct the ultra-rapid delayed rectifier potassium current (IKur). Pharmacological blockade of human Kv1.5 (hKv1.5) has been regarded as an effective treatment of re-entrant based atrial fibrillation, because Kv1.5 is highly expressed in human cardiac atria but scarcely in ventricles. The Kv1.5 blockade is also expected to be used in cancer therapeutics since Kv1.5 is overexpressed in some types of human tumors. Here, we investigated the blockade of hKv1.5 channels by HMQ1611, a novel symmetrical biphenyl derivative. hKv1.5 channels were heterologously expressed in Chinese hamster ovary cells. The effects of HMQ1611 on wild-type and 13 hKv1.5 mutant channels were examined using the whole-cell patch-clamp method, and molecular docking simulation was conducted to predict the docking position of HMQ1611 within Kv1.5 channels. We showed that HMQ1611 reversibly inhibited the hKv1.5 current in a concentration-dependent manner (IC50 = 2.07 M). HMQ1611 blockade of hKv1.5 current developed with time during depolarizing voltage-clamp steps, and this blockade was also voltage-dependent with a steep increase over the voltage range for channel openings. HMQ1611 inhibition was significantly reduced in the T479A, T480A, V505A, I508A, L510A, V512A, and V516A hKv1.5 mutant channels. Molecular docking analysis predicted that V505, V512, and T480 were involved in the blocking action of HMQ1611 on hKv1.5 channels. These results suggest that HMQ1611 inhibits hKv1.5 currents as an open channel blocker. Amino acid residues located at the base of the selectivity filter (T479 and T480) and in the S6 segment (V505, I508, L510, V512, and V516) of hKv1.5 appear to constitute potential binding sites for HMQ1611.